Resource scarcity and information technology: Issues and trends among first-year accounting students. - Papageorgiou, E.; Callaghan, C. (South African Journal of Higher Education, 2014)
Technology is never enough; there will always be the demand for more to manage the present and to gear up for the future. Consequently, engaging in a deliberate search for knowledge is critical to higher education. Higher education institutions (HEIs) encourage the study of the learning environment and ensure that the appropriate management strategies are in place to educate students. In a changing academic environment, computer facilities at HEIs are one of the key drivers. The main aim of this article was to investigate the use of computer facilities among first-year accounting students at the University of the Witwatersrand (Wits). The data was collected over a period of three years (2010, 2011 and 2012). The results of the study revealed the demographics of Accounting I students and their academic performance, use of computer facilities, knowledge of different software packages and other valuable information regarding computer facilities. The study concluded that the use of and exposure to computer facilities influence the academic performance of first-year accounting students.